Towards the access to information regarding the Personal Data Handling: A proposal for improvement and simplification of Privacy and Security Policies - Marialva Yvano, Michel; Coleti, Thiago Adriano; Della Mura, Wellington Aparecido; Fioravante, Carla Carolina; Moreira de Souza, Maria Luiza; Amadeu Teixeira, Larissa; Morandini, Marcelo (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2024: Anais do XXIII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2024)
The emergence of data-driven business models has boosted computational activities supported by the manipulation of personal data, as their capacity to generate information about people (users), their habits and preferences is enormous. Regulations, such as the European Union's General Data Protection Regulation (GPDR) and the Brazilian government's "Lei Geral de Proteção de Dados" (LGPD), require that data subjects receive clear information about the manipulation of their data. However, this information is often contained in long and complex privacy policies, making it difficult for users to access and understand. To ensure Personal Data Transparency, this information must be presented clearly and objectively, facilitating discovery, analysis, and decision-making by data subjects. This work proposes and evaluates a Human-Computer Interaction strategy to improve Personal Data Transparency and promote access to and understanding information by data subjects. Given the difficulties encountered in Privacy Policies, this simplified strategy was proposed, based on User-Centered Design and TR-Model guidelines, to facilitate the access and the use of information. The evaluation of the prototypes involved 42 participants and resulted in a positive score of 77 on the System Usability Scale (SUS). Although the feedback was mostly favorable, the need to improve the consistency of the information presented was highlighted due to the variation between simple and complex data.